2017
DOI: 10.1186/s40878-017-0063-1
|View full text |Cite
|
Sign up to set email alerts
|

Early tracking and immigrant optimism: a comparative study of educational aspirations among students in disadvantaged schools in Sweden and the Netherlands

Abstract: Educational tracking affects both the trajectories and the composition of peers that students meet in school. This study compares the effect of significant others on students’ educational aspirations within two transition regimes: the more comprehensive Swedish system and the more stratified Dutch. Separating between doxic and habituated aspirations, I hypothesize that (1) aspirations among students in disadvantaged schools will be lower in the Netherlands than in Sweden; (2) the higher educational aspirations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 75 publications
1
14
0
1
Order By: Relevance
“…The magnitude of the associations was modest, meaning that the better access to social capital should be seen as an incomplete buffer rather than as a levelling factor. However, both qualitative (Thapar-Björkert & Sanghera 2010) and quantitative (Behtoui 2017;Nygård 2017) studies have previously shown that access to social capital is also associated with educational aspirations. This means that social capital is likely to be more beneficial for education than our results suggest if outcomes are considered more broadly.…”
Section: Discussionmentioning
confidence: 99%
“…The magnitude of the associations was modest, meaning that the better access to social capital should be seen as an incomplete buffer rather than as a levelling factor. However, both qualitative (Thapar-Björkert & Sanghera 2010) and quantitative (Behtoui 2017;Nygård 2017) studies have previously shown that access to social capital is also associated with educational aspirations. This means that social capital is likely to be more beneficial for education than our results suggest if outcomes are considered more broadly.…”
Section: Discussionmentioning
confidence: 99%
“…The index score for the Netherlands is one of the highest in Europe. Nygård (2017) compares the Dutch early and vertically tracked system (also described as multi-tiered secondary education) with the more comprehensive Figure 1. the dutch educational system (source: authors' own figure).…”
Section: The Dutch Education Systemmentioning
confidence: 99%
“…The terms used to denote these resources typically allude to ethnicity, for example ethnic capital (Lee & Zhou, 2017), ethnicity as social capital (Zhou 2005), or ethnicized social capital (Nygård, 2017). However, immigrant communities are often ethnically mixed, and "ethnic businesses" typically cater to multiple ethnicities from the same country or region of origin.…”
Section: Immigrant Networkmentioning
confidence: 99%